Development of a degenerated TaqMan real‐time Q‐PCR for detection of bacteria‐free DNA in dialysis fluid. (15th December 2016) - Bergallo, Massimiliano; Loiacono, Elisa; Rizzo, Giovanna; Caiazzo, Marialuisa; Palladino, Giuseppe; Amore, Alessandro
Abstract: Bacterial‐derived DNA fragments (BDNAs) have been shown to be present in a dialysis fluid, to pass through dialyzer membranes, and to induce interleukin 6 (IL‐6) in mononuclear cells. DNA fragments are thought to be derived from microorganisms inhabiting hemodialysis water and fluid. The primary aim of the present study was to develop two degenerated TaqMan real‐time quantitative‐PCR (Q‐PCR) for detection of a broad range of bacterial DNA that specifically detect 16S ribosomal DNA (rDNA) (862 and 241 bp) and evaluate the efficiency of the Bellco Selecta resin to capture the BDNAs in the dialysis fluid. For this purpose, we decided to compare measurements of unfragmented samples (9.8 × 10 5 Escherichia coli genome) with artificially fragmented DNA samples. We assessed two broad‐range real‐time PCR targeting bacterial 16S rRNA genes for detection of fragmented and unfragmented bacterial DNA in the dialytic fluid and demonstrated that Bellco Selecta resin is capable of retaining these types of bacterial DNA.